2007
DOI: 10.1051/0004-6361:20066169
|View full text |Cite
|
Sign up to set email alerts
|

Arcsecond-resolution $^\mathsf{{12}}$CO mapping of the yellow hypergiants IRC +10420 and AFGL 2343

Abstract: Context. IRC +10420 and AFGL 2343 are the unique, known yellow hypergiants (YHGs) presenting a heavy circumstellar envelope (CSE). Aims. We aim to study the morphology, exceptional kinematics, and excitation conditions of their CSEs, and the implications for mass-loss processes. Methods. We have mapped the 12 CO J = 2−1 and 1−0 emission in these YHGs with the IRAM Plateau de Bure interferometer and the 30 m telescope. We developed LVG models in order to analyze their circumstellar characteristics. Results. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
149
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(169 citation statements)
references
References 33 publications
17
149
3
Order By: Relevance
“…They also show that the model derived by Castro-Carrizo et al (2007) for low-J CO transitions was applicable, with minor changes, to higher excitation lines.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…They also show that the model derived by Castro-Carrizo et al (2007) for low-J CO transitions was applicable, with minor changes, to higher excitation lines.…”
Section: Introductionmentioning
confidence: 60%
“…5. Quintana-Lacaci (2008) showed that the molecular material observed by Castro-Carrizo et al (2007) was only ejected during the YHG phase. No molecular gas expelled from the RSG phase was detected.…”
Section: Introductionmentioning
confidence: 99%
“…None of the YHGs in Wd 1 possess the old (∼4000 yr), massive (M > 1 M ) ejection nebulae seen in HD 179821 and IRC +10 420 (Oudmaijer et al 1996;Castro-Carrizo et al 2007). We suspect that in the extreme environment of Wd 1 such nebulae would quickly be ablated by the cluster wind arising from the OB stars -as appears to be the case for the RSGs W20 and W26 (see Sect.…”
Section: The Yellow Hypergiantsmentioning
confidence: 96%
“…For HD 33579 (A3Ia + ) in the LMC, Stahl et al (1991) (Lobel et al 2003). Castro-Carrizo et al (2007) measure outflow velocities of 35 km s −1 and 25−37 km s −1 for the ejecta associated with HD 179821 and IRC +10 420 (although a priori it is not clear if they were ejected in a RSG or YHG phase). For both these stars, variable mass-loss rates of 4−300 × 10 −5 M yr −1 and 1.2−3 × 10 −4 M yr −1 were found respectively during the nebulae formation events, with Blöcker et al (1999) also reporting a mass-loss rate in excess of 10 −3 M yr −1 for IRC +10 420 in the recent past.…”
Section: The Yellow Hypergiantsmentioning
confidence: 99%
“…Castro-Carrizo et al (2007) mention variations in the mass-loss rate for both hypergiants on time scales of ∼1000 years. In this study, where we only consider CO emission lines measured with single-dish telescopes, we lack sensitivity for the rapid density fluctuations.…”
Section: Variabilitymentioning
confidence: 99%